P251 Environmental fungal sampling in a cystic fibrosis centre. (15th November 2017) - Collier, LJ; Bright-Thomas, RJ; Richardson, M; Jones, AM
Abstract : Objectives: Aspergillus is a ubiquitous organism and CF lungs are vulnerable to infection. Aspergillus is known to be found in high numbers in organic matter and during building works. We commenced environmental fungal air sampling prior to and during building work carried out adjacent to our CF unit to evaluate and monitor our air quality. Methods: An SAS Microbial air sampler sampled 1 cubic metre of air over 5 min in assigned locations throughout our ward on a weekly basis. Outdoor samples were taken during this time for comparison. Each plate was cultured for 4 days at 30°C. Results: The predominant organism was Aspergillus fumigatus, the second Penicillium Spp. Site 1, outdoor air: revealed a maximum yield of 59 colony forming units (CFU) A. fumigatus (range 0–59 CFU, median 9), and 8 CFU Penicillium (0–8, median 0). Site 2, ward corridor: 29 CFU A. fumigatus (0–29 CFU, median 2.5), 15 CFU Penicillium (0–15, median 0.5). Site 3, patient room: 12 CFU A. fumigatus (0–12 CFU, median 2), 9 CFU Penicillium (0–9, median 0). Site 4, positive pressure anteroom: 2 CFU A. fumigatus (0–2 CFU, median 0), 1 CFU Penicillium (0–1 CFU, median 0). Site 5, patient room: 58 CFU A. fumigatus (0–58 CFU, median 4.5), 5 CFU Penicillium (0–5 CFU, median 2.5). There was a clear rise in Aspergillus yield demonstrated during the summer months in all areas except our positive pressure anteroom which persistently yielded negligible fungal growth. Conclusions: High levels of A. fumigatus were persistently yielded from sites 1, 2, 3 and 5, both at baseline and during building works, with peak counts being found in the summer months. Fungal ingress onto the ward was demonstrated in all sites except in our positive pressure anteroom, with ≥10 air changes per hour, leading to isolation rooms. This gives doubts about the efficacy of our ventilation system in the majority of locations throughout our ward and needs to be clinically correlated with patient outcomes.